UPAYA PEMBENTUKAN KARAKTER SISWA MELALUI PENDIDIKAN PANCASILA DISEKOLAH DASAR - Siva Septiani; Rahmawati; Nur Aulia Sabhrina; Auliya Aenul Hayati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe both the process and outcomes of implementing Pancasila Education in developing primary school students’ character. It employs a descriptive quantitative approach, utilizing online surveys completed by fifth and sixth-grade students at SDN 1 Pasawahan, Cirebon Regency. The research instrument was validated by experts and passed a limited trial phase. The results indicate that students’ understanding and application of Pancasila values are in the high category, with an average score of 75 for aspects such as respectful attitude, discipline, independence, responsibility, and national pride. The implementation of Pancasila Education has proven effective in promoting positive behaviors and reducing negative behaviors among students. Major challenges in the Pancasila character-building program include fluctuating learning motivation and limited teacher training, making innovative experiential and technology-based learning crucial. The research recommends active collaboration among schools, teachers, parents, and the community to strengthen the character education environment, alongside the optimization of the Merdeka Curriculum and the Pancasila Student Profile, to nurture a future generation with strong character, creativity, and integrity in societal life.